Clinical pattern and presentation of abnormal uterine bleeding - V., Sarala; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abnormal uterine bleeding (AUB) is a very common debilitating gynecological condition among women of the reproductive age group. This diagnosis is given to women in whom no clear etiology is identified. It can occur in ovulatory and anovulatory cycle. It influences the physical, emotional, sexual and professional life of a woman. This study was carried out to evaluate the clinical profile of abnormal uterine bleeding. Methods: This cross-sectional study was carried out among 350 patients who were clinically diagnosed with AUB for a period of one year from April 2018 to March 2019. Patients with uterine polyp, adenomyosis, Leiomyoma, malignancies and with various coagulopathies were excluded from the study by physical examination, ultrasound, histopathology and blood test. The remaining 280 patients between the ages 20-60 years were selected for clinical classification of AUB. Results: Majority of the participants were in the age group of 41-50 years (60%). AUB is most commonly seen in multiparous women (48.92%). The prominent bleeding pattern seen was menorrhagia (52.2%). Conclusions: Menorrhagia is the most common form of AUB and there is a need to prevent the consequences of menorrhagia by way of creating awareness among the women, and by early diagnosis and clinical management of complications.